2020
DOI: 10.1371/journal.pone.0242398
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of COVID-19: Density matters

Abstract: Physical distancing has been argued as one of the effective means to combat the spread of COVID-19 before a vaccine or therapeutic drug becomes available. How far people can be spatially separated is partly behavioral but partly constrained by population density. Most models developed to predict the spread of COVID-19 in the U.S. do not include population density explicitly. This study shows that population density is an effective predictor of cumulative infection cases in the U.S. at the county level. Daily c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
176
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(192 citation statements)
references
References 20 publications
(24 reference statements)
13
176
2
1
Order By: Relevance
“…Our findings are consistent with previous research that have demonstrated a strong relationship between population density and other infectious diseases [4,6,7,9,35]. In the current SARS--CoV-2 pandemic, recent literature has been conflicting, where some research also suggests a density-dependence of COVID-19 transmission [17,36] and other measures of the severity of the outbreak [19,37], while other research suggests that there are other factors that can better explain the pandemic [18,38]. However, to our knowledge, our results are one of the first to show that population density is an important driver of COVID-19 transmission, even in areas where residents rely more on private modes of transportation.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with previous research that have demonstrated a strong relationship between population density and other infectious diseases [4,6,7,9,35]. In the current SARS--CoV-2 pandemic, recent literature has been conflicting, where some research also suggests a density-dependence of COVID-19 transmission [17,36] and other measures of the severity of the outbreak [19,37], while other research suggests that there are other factors that can better explain the pandemic [18,38]. However, to our knowledge, our results are one of the first to show that population density is an important driver of COVID-19 transmission, even in areas where residents rely more on private modes of transportation.…”
Section: Discussionsupporting
confidence: 91%
“…However, a higher population density in the province was an independent predictor of SARS-CoV-2 seroprevalence when altitude was an adjusted factor. Although population density was not an important factor in COVID-19 spreading under strict lockdown policies [23], it has been also described as a relevant factor for SARS-CoV-2 transmission in less strict conditions [24][25][26][27]; therefore, some effect of population density on transmission in the period before the lockdown in Spain seems plausible.…”
Section: Discussionmentioning
confidence: 99%
“…He reported that population density and employment density were positively correlated with COVID-19 mortality rates. Wand and Li [ 29 ] found that population density mattered in the spreading of COVID-19 on the U.S. county level. They demonstrated that population density alone accounted for up to 76 percent of cumulative infection cases in the U.S. from early March to late May 2020.…”
Section: Literature Reviewmentioning
confidence: 99%